Senegal : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) examines the financial management in both the public and private sectors, aimed as an evaluation, not an audit, and, identifies financial risks within current practices, and procedures in Senegal. It does not however, intend to suggest an accurate, final allocation of public resources, though it facilitates implementation of action plans that reinforce the Government's reform agenda. Within the context of the Country Assistance Strategy (CAS), this CFAA supports the technical and financial partnerships which contribute to the economic, and financial reforms being implemented in the country, and, is an integral part of the Heavily Indebted Poor Countries (HIPC) initiative. One concern is risk evaluation involving the public sector and their partners in budget formulation, preparation, and implementation. Of critical importance is the improvement of public financial management, namely within: external financing; budget preparation and implementation, including internal controls; public accounting and reporting practices; treasury management practices; and wage controls. The CFAA proposes recommendations, and actions to be taken, primarily focusing on building capacity, and strengthening human resources, and, outlines the need to establish concerted efforts, supported by technical, and financial partners, towards integrated investment projects that allow public expenditures - based on a strong budget support - in particular, for social action programs. The first volume contains the main report describing and analyzing the public financial management in Senegal and the private sector accounting profession and NGOs. The second volume contains annexes and is presented only in French.